ANALYZING THE CONTENT OF THE SCIENCE BOOK FOR THE FIRST INTERMEDIATE GRADE ACCORDING TO THE THEORY OF MULTIPLE INTELLIGENCES - Amer Abdul-Hussain Nema , Safa Shaheed Hussain (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The current research has been labeled "analyzing the content of the science book for the first intermediate grade in light of the theory of multiple intelligences."Thus, the current research aims to identify the extent to which the science textbook for the first intermediate grade includes multiple intelligences and the extent to which paragraphs of one intelligence are included in that book, to determine the goal of the research, the two researchers prepared a search tool, which consisted of (53) paragraphs distributed into nine fields (types of intelligence) after being presented to a group of experts and referees in the field of educational and psychological sciences.After preparing the tool and making sure of the validity and reliability of the analysis, the two researchers analyzed the book by using the explicit idea as a unit for recording and repetitions as a unit for enumeration.Taking into consideration a group of important observations in the field of analysis, such as expressions that carry more than one meaning, and when there is confusion in the meaning ... etc., and how to deal with those cases, and then the book was completely analyzed, as the analyzed pages reached (56) pages.After completing the analysis, the data was processed by calculating the frequencies and percentages for all areas of multiple intelligences to achieve the first part of the research goal. Also, the frequencies and percentages of each intelligence paragraph were calculated to achieve the second part of the research goal.A set of results were reached that can be summarized as the content of the book achieved (770) iterations distributed among nine intelligences.Verbal intelligence (linguistic) achieved the highest percentage (23%), while social intelligence achieved the lowest percentage (4%), as for musical intelligence, it did not achieve any percentage in the content of Analyzing the content of the science book for the first intermediate grade according to the theory of multiple intelligences PJAEE, 17 (6) (2020) 15762 the book, according of these results, the researchers developed a set of conclusions, recommendations and proposals.